Trial of remote ischaemic preconditioning in vascular cognitive impairment (TRIC-VCI): protocol. Issue 10 (14th October 2020) - Ganesh, Aravind; Barber, Philip; Black, Sandra E; Corbett, Dale; Field, Thalia S; Frayne, Richard; Hachinski, Vladimir; Ismail, Zahinoor; Mai, Lauren M; McCreary, Cheryl R; Sahlas, Demetrios; Sharma, Mukul; et al.
Abstract : Introduction: Cerebral small vessel disease (cSVD) accounts for 20%–25% of strokes and is the most common cause of vascular cognitive impairment (VCI). In an animal VCI model, inducing brief periods of limb ischaemia-reperfusion reduces subsequent ischaemic brain injury with remote and local protective effects, with hindlimb remote ischaemic conditioning (RIC) improving cerebral blood flow, decreasing white-matter injury and improving cognition. Small human trials suggest RIC is safe and may prevent recurrent strokes. It remains unclear what doses of chronic daily RIC are tolerable and safe, whether effects persist after treatment cessation, and what parameters are optimal for treatment response. Methods and analysis: This prospective, open-label, randomised controlled trial (RCT) with blinded end point assessment and run-in period, will recruit 24 participants, randomised to one of two RIC intensity groups: one arm treated once daily or one arm twice daily for 30 consecutive days. RIC will consistent of 4 cycles of blood pressure cuff inflation to 200 mm Hg for 5 min followed by 5 min deflation (total 35 min). Selection criteria include: age 60–85 years, evidence of cSVD on brain CT/MRI, Montreal Cognitive Assessment (MoCA) score 13–24 and preserved basic activities of living. Outcomes will be assessed at 30 days and 90 days (60 days after ceasing treatment). The primary outcome is adherence (completing ≥80% of sessions). Secondary safety/tolerability outcomes include the per cent of sessions completed and pain/discomfort scores from patient diaries. Efficacy outcomes include changes in cerebral blood flow (per arterial spin-label MRI), white-matter hyperintensity volume, diffusion tensor imaging, MoCA and Trail-Making tests. Ethics and dissemination: Research Ethics Board approval has been obtained. The results will provide information on feasibility, dose, adherence, tolerability and outcome measures that will help design a phase IIb RCT of RIC, with the potential to prevent VCI. Results will be disseminated through peer-reviewed publications, organisations and meetings. Trial registration number: NCT04109963 .